2017
DOI: 10.1007/s10404-017-1970-z
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-static drainage in a network of nanoslits of non-uniform depth designed by grayscale laser lithography

Abstract: Fig. 1 Flowchart of the fabrication process. a Principle of grayscale laser lithography to fabricate varying-depth nanochannels in one step. b Nanochannels are integrated in the nanofluidic chips with standard fabrication steps. c Scheme of the final nanofluidic chip

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…30 It has been shown that the IP rules are still valid in mesoporous materials. 31,32 This model is summarized later. The new features introduced for the present study are described afterward.…”
Section: Drying Algorithmmentioning
confidence: 99%
“…30 It has been shown that the IP rules are still valid in mesoporous materials. 31,32 This model is summarized later. The new features introduced for the present study are described afterward.…”
Section: Drying Algorithmmentioning
confidence: 99%
“…For the monoporous sample LP70, our results show so slow an imbibition rate that they cannot be described by eqn (4). Indeed, we have increased the value of % r in eqn (4) in order to reduce the front velocity, but for values % r 4 400 mm the Jurin height becomes smaller than the observed front heights (see Fig.…”
Section: Imbibition Characteristics Of the Different Porous Mediamentioning
confidence: 64%
“…1 Water absorption is important for food processing (rehydration) and preservation, 2 as well as for the basic process underlying ink writing, where liquids spread on a rough porous substrate, 3 and for microfluidics. 4 Theory of capillary imbibition has been intensively studied since the pioneering works of Bell & Cameron, 5 Lucas 6 and Washburn. 7 They assumed, in agreement with experimental observations, that under the action of capillary effects (Laplace pressure below the interface) a wet front progresses through the sample while saturating the material behind.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, 2.5D microchannels are fabricated by direct grayscale lithography (GSL) to produce funnel shaped geometries with non-uniform width and height. GSL has already been used in microfluidics to obtain complex free-standing shapes 28 or design programmable gradients 29 , valves 30 , and model porous systems 31 , but to the best of our knowledge, it has not been applied to design biosensing systems. An LoD of 4 fM in 30 seconds is achieved with these GSL chips.…”
Section: Introductionmentioning
confidence: 99%